Brain Development of Attachment Experience: How Does It Affects Our Brain? - Rachmat Hidayat; Patricia Wulandari (HM Publisher, 2021)
Our infant experiences involve our emotions, behavior, perceptions, and our mental models of the world of others and ourselves. Implicit memories encode the early forms of our learning about the world. Implicit memories directly shape our experiences here and now with no clue as to their origins from past events. Attachment research, combined with independent findings from our modern studies of genetics and developmental neurobiology, suggests that certain types of communication in emotionally connected relationships offer an essential experience that a child's mind can develop. This literature review describes how our experience in childhood affects brain development.